PEMECAHAN MASALAH LIMBAH LAUNDRY DI SLEMAN DENGAN PROGRAM IPTEK BAGI MASYARAKAT (IbM) - Aminatun, Tien; Padmaningrum, Regina Tutik; Yuliati, - (Universitas Negeri Yogyakarta, 2016)
Karangmalang and Kuningan are the area located near the campus ofYogyakarta State University and Gadjah Mada University. This causes the twoareas have crowded population. Many students from outside of Sleman Yogyakarta stay in many boarding houses that need laundry service since they do not have enough time and are very busy of studying activities. There are approximately 30 laundry service businesses in these areas. The condition has positive impact on local people income generating. However, it also cause adverse effects on the environment because of the laundry waste water directly discharged into the environment without prior treatment. The priority problem to solve is the disposal of waste water and dissemination of eco-friendly detergen. We had